Practical Issues in Developing a Culturally Tailored Physical Activity Promotion Program for Chinese and Korean American Midlife Women: A Pilot Study - Chee, Wonshik (J Med Internet Res, 2016)
BACKGROUND: With advances in computer technologies, Web-based interventions are widely accepted and welcomed by health care providers and researchers. Although the benefits of Web-based interventions on physical activity promotion have been documented, the programs have rarely targeted Asian Americans, including Asian American midlife women. Subsequently, culturally competent Web-based physical activity programs for Asian Americans may be necessary. OBJECTIVE: The purpose of our study was to explore practical issues in developing and implementing a culturally competent Web-based physical activity promotion program for 2 groups of Asian American women—Chinese American and Korean American midlife women—and to provide implications for future research. METHODS: While conducting the study, the research team members wrote individual memos on issues and their inferences on plausible reasons for the issues. The team had group discussions each week and kept the minutes of the discussions. Then, the memos and minutes were analyzed using a content analysis method. RESULTS: We identified practical issues in 4 major idea categories: (1) bilingual translators’ language orientations, (2) cultural sensitivity requirement, (3) low response rate, interest, and retention, and (4) issues in implementation logistics. CONCLUSIONS: Based on the issues, we make several suggestions for the use of bilingual translators, motivational strategies, and implementation logistics.